Helping doctors hasten COVID-19 treatment: Towards a rescue framework for the transfusion of best convalescent plasma to the most critical patients based on biological requirements via ml and novel MCDM methods. (November 2020) - Albahri, O.S.; Al-Obaidi, Jameel R.; Zaidan, A.A.; Albahri, A.S.; Zaidan, B.B.; Salih, Mahmood M.; Qays, Abdulhadi; Dawood, K.A.; Mohammed, R.T.; Abdulkareem, Karrar Hameed; Aleesa, A.M.; Alamoodi, A.H.; et al.
Highlights: Intelligence-integrated concept is proposed to identify the most appropriate CP for corresponding prioritised patients with COVID-19. ABO compatibility is assessed after classifying donors into the four blood types. Contracted patient decision matrix in-between'serological/protein biomarkers and the PaO2 /FiO2 ' and 'patients list'. Proposed a novel subjective and objective decision by opinion score method (SODOSM)'. Contracted CP-decision matrix in-between serological/protein bio-markers criteria and 'CPs tested list'. Abstract: Context: People who have recently recovered from the threat of deteriorating coronavirus disease-2019 (COVID-19) have antibodies to the coronavirus circulating in their blood. Thus, the transfusion of these antibodies to deteriorating patients could theoretically help boost their immune system. Biologically, two challenges need to be surmounted to allow convalescent plasma (CP) transfusion to rescue the most severe COVID-19 patients. First, convalescent subjects must meet donor selection plasma criteria and comply with national health requirements and known standard routine procedures. Second, multi-criteria decision-making (MCDM) problems should be considered in the selection of the most suitable CP and the prioritisation of patients with COVID-19. Objective: This paper presents a rescue framework for the transfusion of the best CP to the most critical patients with COVID-19 on the basis of biological requirements by using machine learning and novel MCDM methods. Method: The proposed framework is illustrated on the basis of two distinct and consecutive phases (i.e. testing and development). In testing, ABO compatibility is assessed after classifying donors into the four blood types, namely, A, B, AB and O, to indicate the suitability and safety of plasma for administration in order to refine the CP tested list repository. The development phase includes patient and donor sides. In the patient side, prioritisation is performed using a contracted patient decision matrix constructed between 'serological/protein biomarkers and the ratio of the partial pressure of oxygen in arterial blood to fractional inspired oxygen criteria' and 'patient list based on novel MCDM method known as subjective and objective decision by opinion score method'. Then, the patients with the most urgent need are classified into the four blood types and matched with a tested CP list from the test phase in the donor side. Thereafter, the prioritisation of CP tested list is performed using the contracted CP decision matrix. Result: An intelligence-integrated concept is proposed to identify the most appropriate CP for corresponding prioritised patients with COVID-19 to help doctors hasten treatments. Discussion: The proposed framework implies the benefits of providing effective care and prevention of the extremely rapidly spreading COVID-19 from affecting patients and the medical sector.